Perlindungan Hukum Pemilik Hak Formulasi Dalam Bisnis Private Label - Akbar, Dimas Fajriansyah; Nasution, Krisnadi (CV. Era Digital Nusantara, 2025)
The private-label manufacturing industry is growing rapidly in response to increasing demands for efficient and flexible production. However, ownership of product formulations within the private-label scheme remains a legally complex issue, particularly concerning intellectual property protection. This study aims to examine the ownership status of product formulas in the private-label business based on trade secret regulations and IP protection in Indonesia. Using a normative legal research method combined with conceptual and statutory approaches, the study explores the legal rights of both the brand owner and the manufacturer over the product formulation. According to Law No. 30 of 2000, a trade secret must have economic value, be unknown to the public, and be protected through reasonable efforts. In practice, the boundaries of ownership often become unclear in the absence of written agreements. This analysis delves into the concept of ownership rights in trade secrets and the potential risks of their violation.